2021
DOI: 10.3389/fphys.2021.714655
|View full text |Cite
|
Sign up to set email alerts
|

Muscle in Variable Gravity: “I Do Not Know Where I Am, But I Know What to Do”

Abstract: Purpose: Fascicle and sarcomere lengths are important predictors of muscle mechanical performance. However, their regulation during stretch-shortening cycle (SSC) activities in usual and challenging conditions is poorly understood. In this study, we aimed to investigate muscle fascicle and sarcomere behavior during drop jumps (a common SSC activity) in conditions of variable gravity.Methods: Fifteen volunteers performed repeated drop jumps in 1 g, hypo-gravity (0 to 1 g), and hyper-gravity (1 to 2 g) during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Consequently, due to insufficient muscle contraction, cross-bridges possibly are detached beyond their SRES ( Ishikawa et al, 2005 ) resulting in lower force generating capacity evidenced by the theoretical sarcomere contextualization. Similarly, during hyper-gravity-induced overload it was shown that the estimated sarcomere operating range shifts towards the ascending limb ( Monti et al, 2021 ). However, it has been shown that forces similar to those at 1 g can be generated after the deceleration phase ( Monti et al, 2021 ), suggesting that mechanically detached cross-bridges may reattach more rapidly during the take-off phase ( Ishikawa et al, 2005 ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Consequently, due to insufficient muscle contraction, cross-bridges possibly are detached beyond their SRES ( Ishikawa et al, 2005 ) resulting in lower force generating capacity evidenced by the theoretical sarcomere contextualization. Similarly, during hyper-gravity-induced overload it was shown that the estimated sarcomere operating range shifts towards the ascending limb ( Monti et al, 2021 ). However, it has been shown that forces similar to those at 1 g can be generated after the deceleration phase ( Monti et al, 2021 ), suggesting that mechanically detached cross-bridges may reattach more rapidly during the take-off phase ( Ishikawa et al, 2005 ).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, during hyper-gravity-induced overload it was shown that the estimated sarcomere operating range shifts towards the ascending limb ( Monti et al, 2021 ). However, it has been shown that forces similar to those at 1 g can be generated after the deceleration phase ( Monti et al, 2021 ), suggesting that mechanically detached cross-bridges may reattach more rapidly during the take-off phase ( Ishikawa et al, 2005 ). Therefore, the data implies that lower pre-activity combined with reduced reflex associated muscle activity ( Helm et al, 2020 ) potentially impairs additional muscle generated contractile force (SRES and RFE effect) due to titin folding ( Eckels et al, 2018 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations